2014
DOI: 10.1108/prt-10-2013-0101
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a low contact angle water-based coating using ultrasonic irradiation

Abstract: Purpose -The key purpose of this study was to investigate the effects of different ultrasonic irradiation times on the wettability and other properties of the resulting water-based coating. The subject water-based coating was prepared using water-soluble polyester and amino resins by ultrasonic oscillation. Design/methodology/approach -The coating was prepared by polymerising polyester and amino resins in water using ultrasonic oscillation. The coating was baked for 40 seconds at 350°C to coalesce and solidify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Water‐soluble polyester was used as the polymer matrix polymerized by phthalic anhydride, neopentyl glycol, trimethylol propane, and trimellitic anhydride . The amino resin, 325 resin, was used as crosslinking agent of the polyester, supplied by Cytec.…”
Section: Methodsmentioning
confidence: 99%
“…Water‐soluble polyester was used as the polymer matrix polymerized by phthalic anhydride, neopentyl glycol, trimethylol propane, and trimellitic anhydride . The amino resin, 325 resin, was used as crosslinking agent of the polyester, supplied by Cytec.…”
Section: Methodsmentioning
confidence: 99%
“…The observed results indicated that the contact angle of polyester coating decreased and the molecular weight of polyester decreased initially and then increased and finally reached stable with an increase in the time of ultrasonication. Where, the molecular structure of polyester and the structure of aggregation state of the cured coating were not changed (Zhang et al , 2014).…”
Section: Introductionmentioning
confidence: 99%